Analysis of antibiotics administration in diabetic ulcer patients at Panembahan Senopati regional hospital Bantul - Putra, Adnal K. P. Husein; Sundari, Sri (International Journal Of Community Medicine And Public Health, 2021)
Background: This study provides an overview of diabetic ulcer infection, antibiotic susceptibility patterns, the most common types of antibiotics, factors influence in antibiotics administrations, and verifying the guideline used of antibiotics. Methods: The research used descriptive analysis combined with interviews. The study was starting from February-March 2021. Eighty-six diabetic ulcer patients were selected considering the inclusion and exclusion criteria. We interviewed seven doctors. Results: 71 bacterias were found with a gram-negative bacteria count of 80.3%- higher than gram-positive bacteria (19.7%). The most common gram-negative bacteria found are Escherichia coli (12.7%) and show the most heightened sensitivity with imipenem (80.7%), while cefuroxime and trimethoprim-sulfamethoxazole show the highest resistance (64.9%). The most common gram-positive bacteria found are Staphylococcus aureus (14.1%), and vancomycin shows the most heightened sensitivity (100%), while penicillin shows the highest resistance (71.4%). The most common single antibiotic administration was ceftriaxone, as well as a combination of two antibiotics, namely ceftriaxone and metronidazole. Conclusions: Escherichia coli was the most gram-negative bacteria, which has the highest sensitivity with imipenem, while Staphylococcus aureus was the most gram-positive bacteria, which has the most heightened sensitivity with vancomycin. The most common single antibiotic administration was ceftriaxone, as well as a combination of two antibiotics, ceftriaxone and metronidazole. Factors that influence antibiotics administration are patient condition, susceptibility testing, training, and advice from colleagues. Every doctor uses different guidelines for diabetic foot ulcer.